Agroecology beyond the statist quo? Transforming U.S. imperial agricultural policy - Graddy-Lovelace, Garrett; Roman-Alcalá, Antonio (Journal of Agriculture, Food Systems, and Community Development, 2024)
First paragraph: Agroecology—with its diverse, multifaceted, and liberatory principles, methods, and commitments—seems incommensurate with the U.S. Department of Agriculture (USDA), with its settler colonial origins, imperial histories, racist legacies, neoliberal hegemonies, and contemporary reproduction of the unjust and ecocidal agricultural status quo. And yet, is it possible to make use of what the behemoth department has to offer, in its attempts, albeit paltry, at reform and restitution? More pressingly, can we engage and demand more from the non-monolithic ministry—call for it to stave off further corporate capture of markets, land, germplasm, data, and water? Can we pressure the USDA to protect farmworkers from exploitation, animals from abuse, cooperatives from corporate co-optation, and small-scale farmers from farmgate price degradation? Is abandoning the USDA tantamount to ceding its resources to agro-industries intent on dispossessing Black, Indigenous, and other essential agricultures? Shouldn’t we at least attempt to obstruct the USDA’s obstructionist international stance, as it thwarts the right to food, climate justice, labor rights, and redistributive reforms globally? . . .